Tazkiyatun nafs (purification of the soul): a psycho-spiritual approach in strengthening marriage relationships - Ahmad, Rosliza; Hassan, Siti Aishah (Photonics, 2015)
Marriage has been seen as an essential tool in creating an ideal society. Through marriage institution, a man and a woman could stay jointly and live through affection and happiness. However, due to the lack of spiritual knowledge and practice, some couples, specifically Muslims married couples, facing marital conflicts that lead to either marital distress or marital dissolution. Therefore, this paper discusses the importance of a psycho-spiritual approach based on Islamic perspective to help Muslims married couples to understand and strengthen their marriage relationships. Four elements of human nature; ruh (spirit), qalb (heart), aql (intellect), and nafs (soul), will be discussed to understand the nature of human beings. This paper will examine how these four elements influence Muslim married couples‟ personality in order to be affective couples. In addition, the spiritual practices of tazkiyatun nafs (purification of the soul) will be presented to assist Muslim couples fulfill their responsibilities as the vicegerents of Allah SWT on earth.